Implementing the Efficient Allocation of Pollution - Duggan, John; Roberts, Joanne (American Economic Review, 2002)
We provide simple mechanisms to implement the efficient allocation of pollution, first assuming complete information across firms and then allowing for incomplete information. Both mechanisms operate by inducing firms to monitor one another, using firms’ reports to determine pollution allotments and transfers. The complete information mechanism determines a firm’s transfer according to a linear pollution price, set by other firms. Both mechanisms can be modified to be budget-balanced, in and out of equilibrium. The complete information mechanism implements the efficient allocation even when firms are allowed to use mixed strategies. Under a “single-crossing” condition, the same holds for the incomplete